User's verification to prevent malicious access in web-based forums - Tabar, Mahdi Taheri (2013)
This paper aims to address the issue of malicious accounts that are created and used to imitate real users in web-based forums. In fact, form bots are used to create fake users on forums for several purposes. As a result hundreds of fake users start appearing in the forums and normally placing spam URLs. For forum administrators/managers/moderators, it is a frustrating job to keep members’ list clean. In order to overcome this issue, a novel approach is proposed that would be useful in order to prevent malicious users’ access and decrease rate of deception in web-based forums. We present a comparison between the proposed approach and IDology approach. The results illustrate that our proposed approach addresses the issue more efficiently as compared with IDology approach.